Quando le parole diventano ciottoli. Alcune riflessioni sulla dissociazione mentale - Calesini, Irene (Il sogno della farfalla, 2006)
The article focuses on one symptom of schizophrenia which is ignored nowadays from a psychopathological and diagnostic point of view: mental dissociation. Mention is briefly made of the reasons for such lack of interest, with the exception of a few cases, on the part of the psychiatric world towards this phenomenon. The author distinguishes verbal dissociation, which depends on an illness of the thought and also involves non-conscious thinking, from linguistic disorders with organic causes and typical of neurological syndromes, which at times seem similar in nature. In the clinical context the distinction is made between dissociative phenomena of the conscience (which correspond to symptoms once grouped under the diagnostic category of “hysteria” and which are the only ones considered in the DSM IV classification) and mental dissociation present in schizophrenia. Referring to the research into the origin of human language and its pathology, based on the theoretical work and psychotherapeutic practice of M. Fagioli’s Collective Analysis, the author proposes some reflections on the origin of mental dissociation, considering it both in its verbal expression (schizophasia) and its behavioural form. On the basis of the above-mentioned research, a “precarious structuring” of non-conscious reality, formed in the first year of life, is at the basis of this phenomenon. It is suggested that such a precarious structuring is the result of a precocious non-conscious dynamic between a particular internal reality of the adult which is sick (lack of affectivity) and the vitality and interior image of the baby.